Research Sampling Size System (RSST) / Tuan Badrol Hisham Tuan Besar, Sharidatul Akma Abu Seman and Ahmad Rais Mohamad Mokhtar - Tuan Besar, Tuan Badrol Hisham; Abu Seman, Sharidatul Akma; Mohamad Mokhtar, Ahmad Rais (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
It is a requirement for the undergraduate students to conduct a research as a partial fulfilment of their academic program. However, some students have experienced difficulties in accurately determining the required sample size for their studies. Most of them have made reference to a specific table which might not be so accurate under certain number of constraints; number of population, the level of precision required, the chosen type of sampling technique, the chosen type of data collection method, and others. Therefore, this project is intended to provide assistance to the undergraduate students so that the results of their studies might be more representative of the population. The project is unique from the existing application since it considers the most constraints involved in determining the sample size. It is expected that the project will bring a great relief for students, lecturers and researchers in conducting a more meaningful research for the benefit of the society and the nation in genera.